Conflict Of Cultures Reflected In Hanif Kureishi's The Black Album: A Sociological Approach - Indriani, Yulistia, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
The main aim of this study is to find how conflict of cultures is reflected in Hanif Kureishi's The Black Album by correlating its structural elements and social historical background of England in late of twentieth century. Indeed, literature and sociology are bound each other due to the assumption that the appearance of literary work is not in social emptiness. This study uses qualitative method in which the data are taken from both primary and secondary data source in form of words, sentence and phrases. Primary data source is Hanif Kureishi's The Black Album meanwhile secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. The outcomes of this study are as follows: (1 ) Hanif Kureishi writes The Black Album as the mirror of England society through the structural elements of the novel to reflects the social realities. (2) The Black Album is a social document of the England society in which collision of value and belief between native culture and imigrant culture become the main issues of the country. (3) Hanif Kureishi wrote the novel to critisize the Western people not to disciminate imigrant people.